MENGINTIP KONDISI PERUSAHAAN MELALUI “GOING CONCERN” - Hendro Sasongko; May Mulyaningsih; Obed Fernando Harefa (Universitas Pakuan, 2019)
The research sample consisted of 3 companies with a five year observation period. This research purposed to examine the effect of financial health and company growth on going concern audit opinion either partially or simultaneously. The population of this research is six cement sub-sector companies listed on the Indonesia Stock Exchange from 2013-2017. Data is processed with the Altman Z Score using Binary Logistic Regression analysis tools. The test results show that the financial health condition of the company, which is proxied by the Altman Z Score, significantly influences the acceptance of going concern audit opinion. Company growth, which is proxied by the Sales Growth Ratio, has a significant effect on ongoing concern audit opinion. The condition of financial health and company growth jointly influence the acceptance of going concern audit opinion.